2015
DOI: 10.1111/cen.12828
|View full text |Cite
|
Sign up to set email alerts
|

Role of RAI in the management of incidental N1a disease in papillary thyroid cancer

Abstract: Background Following total thyroidectomy (TT) for papillary thyroid cancer (PTC), pathological assessment can occasionally reveal incidental perithyroidal lymph nodes (LNs) with occult metastases. These cN0pN1a patients often receive radioactive iodine (RAI) therapy for this indication alone. The aim of this study was to determine the central compartment nodal recurrence-free survival in patients treated without RAI compared to those who received RAI treatment. Methods An institutional database of 3664 previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…This study describes a clinical scenario faced by surgeons who do not routinely perform prophylactic central neck dissections, and should be seen as raising the very practical question of whether positive incidental LNs should be considered differently from positive LNs obtained as part of a planned central neck dissection. Our results contrast with the findings of the only other study on the subject of incidental positive LNs, in which there was a recurrence rate of 5.8% after 5 years . This is lower than in our study, where 17% (7/42) of patients with iLNM had recurrent disease.…”
Section: Discussioncontrasting
confidence: 99%
“…This study describes a clinical scenario faced by surgeons who do not routinely perform prophylactic central neck dissections, and should be seen as raising the very practical question of whether positive incidental LNs should be considered differently from positive LNs obtained as part of a planned central neck dissection. Our results contrast with the findings of the only other study on the subject of incidental positive LNs, in which there was a recurrence rate of 5.8% after 5 years . This is lower than in our study, where 17% (7/42) of patients with iLNM had recurrent disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Although our study reveals that skip metastasis can be seen in mPTC, Chae et al 20 reported that 26 per cent of patients with mPTC received potentially unnecessary RAI. In addition, Wang et al 21 reported that in the selected PTC patients with incidental central compartment nodal disease, there is no difference in the five-year central compartment nodal recurrence-free survival in patients treated without RAI compared with those who received RAI treatment. Indeed, a careful follow-up for lateral LNs after surgery may solve these controversies in clinical practice, but further prospective studies are needed in this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Wang and cols. demonstrated that properly selected patients, even with affected lymph nodes, should not necessarily receive RRA (30,31).…”
Section: Discussionmentioning
confidence: 99%